OGLE-2014-BLG-0221Lb: A Jupiter Mass Ratio Companion Orbiting Either a Late-type Star or a Stellar Remnant - Rintaro Kirikawa; Takahiro Sumi; David P. Bennett; Daisuke Suzuki; Naoki Koshimoto; Shota Miyazaki; Ian A. Bond; Andrzej Udalski; Nicholas J. Rattenbury; Leading Authors; Fumio Abe; Richard Barry; et al. (The Astronomical Journal, 2024)
We present the analysis of the microlensing event OGLE-2014-BLG-0221, a planetary candidate event discovered in 2014. The photometric light curve is best described by a binary-lens single-source model. Our light-curve modeling finds two degenerate models, with event timescales of t _E ∼ 70 days and ∼110 days. These timescales are relatively long, indicating that the discovered system would possess a substantial mass. The two models are similar in their planetary parameters with a Jupiter mass ratio of q ∼ 10 ^−3 and a separation of s ∼ 1.1. Bayesian inference is used to estimate the physical parameters of the lens, revealing that the shorter timescale model predicts 65% and 25% probabilities of a late-type star and white dwarf host, respectively, while the longer timescale model favors a black hole host with a probability ranging from 60% to 95%, under the assumption that stars and stellar remnants have equal probabilities of hosting companions with planetary mass ratios. If the lens is a remnant, this would be the second planet found by microlensing around a stellar remnant. The current separation between the source and lens stars is 41–139 mas depending on the models. This indicates the event is now ready for high-angular-resolution follow-up observations to rule out either of the models. If precise astrometric measurements are conducted in multiple bands, the centroid shift due to the color difference between the source and lens would be detected in the luminous lens scenario.